2023
DOI: 10.1111/hae.14785
|View full text |Cite
|
Sign up to set email alerts
|

Low dose emicizumab prophylaxis in haemophilia a patients: A pilot study from India

Abstract: Switzerland) is a recombinant, humanised, bispecific monoclonal antibody, which mimics the haemostatic function of activated factor VIII (FVIIIa) in the tenase complex. 1 It is currently the only globally approved non-factor replacement product for treatment in people with haemophilia A (PwHA). The dose of emicizumab, according to the registered drug label, is 3 mg/kg subcutaneous, once weekly (Q1W) for the first 4 weeks (loading dose), followed by maintenance doses of 1.5 mg/kg every week (Q1W), 3 mg/kg every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A previous case series report 22 showed the effectiveness of monthly emicizumab prophylaxis dose as low as 1.05-1.66 mg/kg and even without loading doses, yet their median ABR still decreased from a baseline of 27.0-4.0. In a pilot study from India 23 including eight patients with severe HA on low-dose emicizumab prophylaxis (.84-2.6 mg/kg/4 weeks), all patients had zero treated bleeds. In addition, earlier Japanese 24 and Finnish studies 25…”
Section: Discussionmentioning
confidence: 99%
“…A previous case series report 22 showed the effectiveness of monthly emicizumab prophylaxis dose as low as 1.05-1.66 mg/kg and even without loading doses, yet their median ABR still decreased from a baseline of 27.0-4.0. In a pilot study from India 23 including eight patients with severe HA on low-dose emicizumab prophylaxis (.84-2.6 mg/kg/4 weeks), all patients had zero treated bleeds. In addition, earlier Japanese 24 and Finnish studies 25…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the cost to less than 25% of the conventional emicizumab prophylaxis cost with relatively good clinical outcome will allow more patients to be on prophylaxis with this highly effective drug. 18,19…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…In some Asian countries with resource‐constrained settings such as Thailand and India, lower dosage of emicizumab has been used with good clinical efficacy. Reduction of the cost to less than 25% of the conventional emicizumab prophylaxis cost with relatively good clinical outcome will allow more patients to be on prophylaxis with this highly effective drug 18,19 …”
Section: Management Of People With Haemophiliamentioning
confidence: 99%
“…Low-dose emicizumab was effective in patients with HA, with or without inhibitors, who performed low bleeding risk activities [ 52 ]. A recent single-center, pilot study conducted in India on a small group of eight patients with HA showed that emicizumab administration at a low dose of 0.84-2.6 mg/kg once every four weeks was effective in reducing bleed rates throughout the follow-up period of one year; there was no evidence of reported bleeding events during the prophylaxis period [ 53 ]. In this study, the patients were exposed to low-impact physical activities such as swimming, cycling, and walking.…”
Section: Reviewmentioning
confidence: 99%